Implementasi Moderasi Beragama Dalam Jaringan Lintas Iman di Kota Surabaya - Setiawan, Dedik (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
This research discusses the process of implementing the ideology of religious moderation carried out by interfaith community networks in the city of Surabaya. The application of the principles of religious moderation carried out by these communities is influenced by many factors ranging from the vision and mission of each community to movements carried out by important figures known as actants. Several actants from each community then networked with each other to harmonize the process of implementing religious moderation and the massive impact of their movement on the people of Surabaya City. The problems and discussions in this research are: 1) How is religious moderation implemented within the scope of community organizations in Surabaya? 2) How does the network of community organizations in Surabaya implement the values ​​of religious moderation? This research uses a qualitative approach which requires in-depth understanding, theory development, and accurate data and information from the source. Data collection used in this research includes: observation, interviews and documentation. The analysis of this research provides an understanding that the implementation of religious moderation carried out by interfaith organizations in the city of Surabaya is moving in the construction of an inter-community network. Where each community is represented by one or more people as actors, liaisons, and even representatives of the organization itself.